The Pug Who Wanted to Be a Mermaid - Swift, Bella (Simon & Schuster Children's Publishing, 2022)
Intro – Title Page – Chapter One – Chapter Two – Chapter Three – Chapter Four – Chapter Five – Chapter Six – Chapter Seven – Chapter Eight – Copyright. Peggy the pug is going on vacation to the seaside! Her special friend Chloe is excited, too, and hopes that she'll see a mermaid. But even though Chloe and Peggy search the beach, they can't find a mermaid anywhere. Not wanting her friend to be disappointed, Peggy decides that she'll just have to become a mermaid herself! But that means that she's going to have to learn how to doggy paddle
Description based on publisher supplied metadata and other sources
Keywords: Dogs-Fiction; Human-animal relationships-Fiction; Mermaids-Fiction; Pug; Dogs; Mermaids; Human-animal relationships; Wishes; Electronic books; Carlin - Romans; nouvelles; etc. pour la jeunesse; Chiens - Romans; nouvelles; etc. pour la jeunesse; Sirènes - Romans; nouvelles; etc. pour la jeunesse; Relations homme-animal - Romans; nouvelles; etc. pour la jeunesse; Souhaits - Romans; nouvelles; etc. pour la jeunesse; Animal fiction; Fiction; Humorous fiction; Juvenile works